The Implementation Of Geogebra : The Capability Of Students In Mathematical Communication For Primary Student - Ladysa, Dina (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2012)
The result of international research as Program for International Students Assessment (PISA) in 2006 and The Trends in International Mathematics and Science Study (TIMSS) in 2007 give the same result. Indonesia students in a row get rank 52 from 57 country, and 36 from 48 country that follow the competation. From the result, should be innovation in teaching to enhance the competence of students. One of alternative is using sofware Geogebra, it caused as an hypotesis of me. There are three reasons, that’s why choos MatLab (1) Geogebra is powerful , that can give the best visual that can enhance mathematical communication. (2) Geogebra can related with the real word (3) Geogebra is famous software. As we know that there are five indicators for mathematical communication. For this article, work sheet that writer explore just the capability conjecture, and generalatation of students. In reality, all of indicator of mathematical communication can be explored using geogebra because the characteristic of geogebra that can be representated all of indicators of mathematical communication.